Al-Ehtbak by Al-Suyuti- Analytical descriptive study - - Al-Munifi, Ahmad bin Sulaiman bin Ahmad (Dirasat: Human and Social Sciences, 2024)
Objectives: This research aims at the theoretical study of the term (Al-Ehtbak), by defining it linguistically and reforming it, and mentioning its coiner with an indication of the number of places in which this art was used in the Holy Qur’an. Subsequently, it conducts a descriptive-analytical study of it in the works of Al-Suyuti, exploring its treatment in his writings on Quranic sciences and rhetoric, aiming to formulate an accurate understanding of its significance within this field. Methods: The researcher used the descriptive and analytical approaches, where he studied the term in question, then investigated the existence of Al-Suyuti’s words about this science, then collected, analyzed and studied it. Results: The research consolidates the various definitions of (Al-Ehtbak), adopting Al-Baqa’i'’s terminology: "Presenting two statements, each supporting the other, with each containing evidence of what is omitted in the other." Among the first who coined this term to denote this rhetorical art was Ismail bin Muhammad Ibn Hani Al-Lakhmi Al-Gharnati. Recommendations include further exploration of the impact of (Al-Ehtbak) in guiding interpretative statements and a reexamination of Al-Suyuti's book “Nazm Al-Badi’ in Praise of the Best Intercessor”. Conclusions: The research elucidates the linguistic and contextual meanings of (Al-Ehtbak) identifying its coiner and detailing the initial usage of this rhetorical device in the Holy Quran. The study adopts a descriptive-analytical approach to scrutinize this term in the works of Al-Suyuti, spanning across his various writings. Additionally, it incorporates insights from previous literature on the topic discovered during the research process.